296HUKUMAN KEBIRI TERHADAP PELAKU TINDAK PIDANA PEMERKOSAAN ANAK DAN KAITANNYA DENGAN HAK ASASI MANUSIA - Wahyuni, Fitri (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
The phenomena of rape against children are very alarming in today's society. The Penal Code and the Child Protection Act has posted punishment on the perpetrator, but there are some disadvantages that arise when legal sanctions are imposed on child rapist. Criminal sanctions against rapist are deemed not provide a deterrent effect. The government passed perpu on castration punishment for child rapist. The castration punishment was a punishment that shows revenge way of thought, so the approach has long been abandoned. In addition, from the objective of sentencing, castration punishment has not yet reflected the sense of justice. Since it has not provided a deterrent effect for offenders and unbalanced with the principles of the right to accommodate the rights of the sustainability of offspring for the offender.Keywords: castration, rape, human rights